Calidad del servicio y el desarrollo del turismo en el balneario Bellavista Nanay, Iquitos 2023 - Florindez Cardenas, Ingrid Nicole (2024)
The objective of this report was to determine the relationship between service quality and tourism development in the Bellavista Nanay Spa, Iquitos 2023, using an applied research methodology with a non-experimental correlational design. The sample consisted of 375 tourists, and the survey technique was employed alongside a questionnaire as the data collection instrument. The results revealed that 45% of tourists considered the service quality to be average, while 26% rated it as high, mainly due to the satisfactory state of the infrastructure, including platforms, streets, and buildings. Regarding tourism development, it was observed that 49% of respondents placed it at a medium level, followed by 18% who perceived it as low, with recurring concerns about the lack of adequate signage on transit routes. Additionally, a significant correlation was identified between the variables studied, evidenced by a strong positive correlation coefficient (r = 0.843; p = 0.000).